China returns to Africa a rising power and a continent embrace - Alden, Chris 1959- (Hurst, 2008)
Addressing the key issues in contemporary China-Africa relations, this title moves beyond narrow media-driven concerns to offer a survey of China's return to Africa, examining what this new relationship holds for diplomacy, trade and development.
Keywords: Wirtschaft; Wirtschaftspolitik; Außenpolitik; Wirtschaftsbeziehungen; Außenhandel; Diplomatie; Afrika; Africa -- Economic conditions -- 21st century; Africa -- Economic policy -- 21st century; Africa -- Relations -- China; China -- Economic conditions -- 2000-; China -- Economic policy -- 2000-; China -- Relations -- Africa; China; Konferenzschrift -- 2006 -- Cambridge